Hubungan Tingkat Pengetahuan Tanda Bahaya Kehamilan pada Ibu Hamil Trimester III Dengan Kepatuhan Melakukan Antenatal Care di Puskesmas Bantal - Pita Marpaung; Berlian Kando Sianipar; Yesi Putri (Jurnal Pakar Kesehatan, 2026)
Antenatal care is regular care for pregnant women with the aim of monitoring the emergence of diseases or adverse conditions that may occur during pregnancy and childbirth. According to the WHO, the global maternal mortality ratio (MMR) is 189 per 100,000 live births. The World Health Organization (WHO) estimates that approximately 15% of all pregnant women will develop complications related to their pregnancy, which can result in maternal and fetal death (WHO, 2023). The purpose of this study is to determine a correlation between knowledge level of pregnancy danger signs in third trimester pregnant women and compliance with antenatal care at Bantal Health Center. The research method used quantitative data with a sample size of 39 third trimester pregnant women. The independent variable was knowledge of pregnancy danger signs in pregnant women, and the dependent variable was compliance with antenatal care. Data analysis in this study used the Chi-Square statistical test (α=0.05). The results of the study showed that most of the respondents, namely 20 (51.3%) respondents, had good knowledge at Bantal Health Center. Most of the respondents, namely 22 (56.4%) respondents, were not compliant in attending ANC at Bantal Health Center. The chi-square test results obtained a p-value of 0.001, meaning that Ha is accepted, indicating that there was a correlation between the knowledge level of pregnancy danger signs in third trimester pregnant women and compliance with antenatal care at Bantal Health Center. The conclusion of this study is that regular pregnancy check-ups are necessary for pregnant women at BPM, health centers, hospitals, and other health care facilities to increase pregnant women's knowledge about danger signs of pregnancy and compliance with antenatal care.